Does water availability regulate biomass partitioning between trunk and branches?. (11th September 2017) - Magnin, A.; Torres, C. D.; Villalba, R.; Puntieri, J. G.
Abstract: The extent to which a vertical trunk is differentiated from its branches is a key trait for the architecture of trees and may affect interspecific relationships. In this study, we analysed the effect of soil water availability on biomass partitioning for Nothofagus pumilio by means of a nursery experiment. Juvenile trees were subject to three irrigation conditions: no irrigation, intermediate irrigation and high irrigation. Irrigation conditions emulated the mean precipitation of the most representative environments inhabited by N. pumilio . Changes in soil water availability modified the biomass partitioning patterns of trees. In comparison to the other two conditions, high irrigation caused: (i) a higher ratio of biomass partitioning to stems than roots; (ii) more trunk growth in relation to its branches; and (iii) more photosynthetic organs relative to the aboveground biomass. Trunk size relative to that of its most recent branches was not increased by water availability. Water availability may play a significant role in the capacity of N. pumilio for space occupation due to the effects on axis differentiation.